Design and Optimization of a Process for Sugarcane Molasses Fermentation by Saccharomyces cerevisiae Using Response Surface Methodology - El-Gendy, Nour Sh.; Madian, Hekmat R.; Abu Amr, Salem S. (Hindawi Publishing Corporation, 2013)
Astatisticalmodelwas developed in this study to describe bioethanol production through a batch fermentation process of sugarcane molasses by locally isolated Saccharomyces cerevisiae Y-39. Response surface methodology RSM based on central composite face centered design CCFD was employed to statistically evaluate and optimize the conditions for maximum bioethanol production and study the significance and interaction of incubation period, initial pH, incubation temperature, and molasses concentration on bioethanol yield.With the use of the developed quadraticmodel equation, amaximumethanol production of 255 g/L was obtained in a batch fermentation process at optimum operating conditions of approximately 71 h, pH 5.6, 38∘C, molasses concentration 18%wt.%, and 100 rpm.